Incentives as connectors: insights into a breastfeeding incentive intervention in a disadvantaged area of North-West England - Thomson, Gill (BioMed Central, 2012)
BACKGROUND: Incentive or reward schemes are becoming increasingly popular to motivate healthy lifestyle behaviours. In this paper, insights from a qualitative and descriptive study to investigate the uptake, impact and meanings of a breastfeeding incentive intervention integrated into an existing peer support programme (Star Buddies) are reported. The Star Buddies service employs breastfeeding peer supporters to support women across the ante-natal, intra-partum and post-partum period. METHODS: In a disadvantaged area of North West England, women initiating breastfeeding were recruited by peer supporters on the postnatal ward or soon after hospital discharge to participate in an 8 week incentive (gifts and vouchers) and breastfeeding peer supporter intervention. In-depth interviews were conducted with 26 women participants who engaged with the incentive intervention, and a focus group was held with the 4 community peer supporters who delivered the intervention. Descriptive analysis of routinely collected data for peer supporter contacts and breastfeeding outcomes before and after the incentive intervention triangulated and retrospectively provided the context for the qualitative thematic analysis. RESULTS: A global theme emerged of 'incentives as connectors', with two sub-themes of 'facilitating connections' and 'facilitating relationships and wellbeing'. The incentives were linked to discussion themes and gift giving facilitated peer supporter access for proactive weekly home visits to support women. Regular face to face contacts enabled meaningful relationships and new connections within and between the women, families, peer supporters and care providers to be formed and sustained. Participants in the incentive scheme received more home visits and total contact time with peer supporters compared to women before the incentive intervention. Full participation levels and breastfeeding rates at 6-8 weeks were similar for women before and after the incentive intervention. CONCLUSION: The findings suggest that whilst the provision of incentives might not influence women's intentions or motivations to breastfeed, the connections forged provided psycho-social benefits for both programme users and peer supporters.